Impact of social media on e-commerce - Manohar Singh, Dr; Singh, Gobindbir (International Journal of Engineering and Technology, 2018)
Social network has gained remarkable attention in the last decade and as the evolution take place, accessing social network sites such as Twitter, Facebook, LinkedIn, Instagram and YouTube have become very affordable. As a large population uses one or the other social networking site, it has become very convenient for companies to reach their consumers through these sites. The main objective of this project is to identify the role of social media marketing strategy and evaluate its importance over traditional marketing strategy in building brand names and consumer behavior. The dataset on which the study has been carried out consists of a sample of tweets on @SamsungMobile, the quar-terly sales of @Samsung Mobile and the information of its followers on Twitter. The analysis and findings of the study highlighted the geo-graphical distribution of the followers of @Samsung Mobile, the market outreach of the brand, and the relationship between the increase in followers and the quarterly sales of @Samsung Mobile.Â Â